Respuesta :

Answer:

GCF: (x + 2)(9x + 6)

Step-by-step explanation:

Given the algebraic expression, 9x(x + 2) + 6(x + 2), where the greatest common factor (GCF) must be taken out:

Solution:

Since (x + 2) are common between the two groups, then we can group 9x and 6 together.

In other words:

= 9x(x + 2) + 6(x + 2)  

= (9x + 6)(x + 2)

If we perform the FOIL method onto (9x + 6)(x + 2), it will result in the following trinomial:

(9x + 6)(x + 2)

= 9x² + 18x + 6x + 12

= 9x² + 24x + 12

Verify Solution:

In order to see why this works, let's go back to the original problem, as if we're trying to determine the resulting trinomial:

Given:  9x(x + 2) + 6(x + 2)  

Distribute 9x and 6 into the parenthesis:

= 9x² + 18x + 6x + 12

Combine like terms:

= 9x² + 24x + 12    ⇒ As we can see, this trinomial matches our solution.

Therefore, the correct answer is: (x + 2)(9x + 6).  

ACCESS MORE
EDU ACCESS
Universidad de Mexico